Global Citizenship and Vulnerability (Revista Iberoamericana de Bioética, 2023)
The current context of global uncertainty and instability in relation to political, economic, migratory and ecological concerns could be an opportunity to look more deeply into the concept of global citizenship, as existing approaches to engagement and interdependence seem increasingly insufficient to address the scope, scale and intensity of the many challenges we face. One heuristic tool for such a task is the concept of vulnerability, as used in bioethics today. We shall further develop this idea in the context of global bioethics.
Keywords: global citizenship; vulnerability; bioethics